2004
DOI: 10.1007/s00213-004-1809-7
|View full text |Cite
|
Sign up to set email alerts
|

The activity of pramipexole in the mouse forced swim test is mediated by D2 rather than D3 receptors

Abstract: Taken together, these studies suggest that the D2 receptor rather than the D3 receptor is important for the antidepressant-like activity observed for pramipexole in the mouse forced swim test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Locomotor activity Locomotor activity was performed as previously described (Siuciak and Fujiwara 2004). Separate groups of mice were used for all locomotor studies.…”
Section: Methodsmentioning
confidence: 99%
“…Locomotor activity Locomotor activity was performed as previously described (Siuciak and Fujiwara 2004). Separate groups of mice were used for all locomotor studies.…”
Section: Methodsmentioning
confidence: 99%
“…This (Favier et al, 2014;Schulte-Herbruggen et al, 2012;Siuciak and Fujiwara, 2004) and in clinical trials alone (Barone et al, 2010) or in combination with L-DOPA (Rektorova et al, 2005). In autoradiography studies PPX binding was shown to be high also in mesolimbic areas like the nucleus accumbens, olfactory tubercle and amygdala.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
“…Besides its effect on PD motor symptoms (Ferger et al, 2010;Lagos et al, 1998), PPX has also been shown to have antidepressant effects in animal models of PD (Schulte-Herbruggen et al, 2012;Siuciak and Fujiwara, 2004) and in clinical trials, alone (Barone et al, 2010) or combined with L-DOPA (Rektorova et al, 2005). L-DOPA alone did not show any anti-depressive or anxiolytic effects (Eskow Jaunarajs et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The results on behavior in the novel and familiar environments in the present study resemble those found for other dopamine D 2 -receptor agonists. Thus, it was found that pramipexole decreases locomotor behavior in rats and mice in a novel environment in low doses, but increases motor activity in a familiar environment in higher doses (3.2 mg/kg) [79,80] . These lines of evidence support the view, that exogenous DA, applied via the nasal route, exerted its behavioral effects by actions on D 2 -receptors, although participation of D 1 -or D 3 -receptors cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%